RIPK3-Mediated Necroptosis and Neutrophil Infiltration Are Associated with Poor Prognosis in Patients with Alcoholic Cirrhosis - Zhenzhen Zhang; Guomin Xie; Li Liang; Hui Liu; Jing Pan; Hao Cheng; Hua Wang; Aijuan Qu; Yan Wang (Journal of Immunology Research)
Alcoholic cirrhosis is an end-stage liver disease with impaired survival and often requires liver transplantation. Recent data suggests that receptor-interacting protein kinase-3- (RIPK3-) mediated necroptosis plays an important role in alcoholic cirrhosis. Additionally, neutrophil infiltration is the most characteristic pathologic hallmark of alcoholic hepatitis. Whether RIPK3 level is correlated with neutrophil infiltration or poor prognosis in alcoholic cirrhotic patients is still unknown. We aimed to determine the correlation of RIPK3 and neutrophil infiltration with the prognosis in the end-stage alcoholic cirrhotic patients. A total of 20 alcoholic cirrhotic patients subjected to liver transplantation and 5 normal liver samples from control patients were retrospectively enrolled in this study. Neutrophil infiltration and necroptosis were assessed by immunohistochemical staining for myeloperoxidase (MPO) and RIPK3, respectively. The noninvasive score system (model for end-stage liver disease (MELD)) and histological score systems (Ishak, Knodell, and ALD grading and ALD stage) were used to evaluate the prognosis. Neutrophil infiltration was aggravated in patients with a high MELD score (≥32) in the liver. The MPO and RIPK3 levels in the liver were positively related to the Ishak score. The RIPK3 was also significantly and positively related to the Knodell score. In conclusion, RIPK3-mediated necroptosis and neutrophil-mediated alcoholic liver inflammatory response are highly correlated with poor prognosis in patients with end-stage alcoholic cirrhosis. RIPK3 and MPO might serve as potential predictors for poor prognosis in alcoholic cirrhotic patients.